Study of Kynematics and Dynamics in the Traffic of Rembangan Tourism in the Jember Regency as Learning Resources for Physics Learning in the Senior High School - Alfido Fauzy Zakaria; Bambang Supriadi; Trapsilo Prihandono (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
One branch of physics is mechanics. Based on interviews to Senior High School teacher in Jember, mechanics is difficult to learn. The eksternals factor this chapter is dificult to learn is learning Resources. The learning Resources are often less contextuall with around the phenomenon of students. The contextuall learning Resources in the Jember Regency is study of kynematics and dynamics in the traffic of Rembangan Tourism. From this experiment, we get data can be used as a learning resources chapter uniform rectilinear motion, decelerated uniform rectilinear motion, accelerated uniform rectilinear motion, Newton’s Law, and circular motion.